Communication Management - Pollák, František; Soviar, Jakub; Vavrek, Roman (IntechOpen, 2022)
Communication Management is an edited volume of chapters written by scholars researching various areas of marketing and management sciences. It presents several issues of marketing management within the limits of marketing communication. Starting from the issue of communication channels and basic sensory apparatus for processing information and stimuli, the book continues with a description of the issue of social media in the time of accelerated digitization. The last chapter introduces the reader to the issue of marketing communication in a sharply non-standard environment. The topic itself creates the opportunity to seek qualitative knowledge for future in-depth research into the impact of the COVID-19 pandemic on both national and transnational economies.